1998
DOI: 10.1002/hep.510280404
|View full text |Cite
|
Sign up to set email alerts
|

Risk of liver and other types of cancer in patients with cirrhosis: A nationwide cohort study in Denmark

Abstract: Cancer risk in patients with cirrhosis could be modified by factors such as changes in hormonal levels, impaired metabolism of carcinogens, or alteration of immunological status. We investigated the risk of liver and various forms of cancer in patients with cirrhosis in a follow-up study. We identified 11,605 1-year survivors of cirrhosis from the files of the Danish National Registry of Patients (NRP) from 1977 to 1989. Occurrence of cancer through 1993 was determined by linkage to the Danish Cancer Registry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
207
10
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(241 citation statements)
references
References 29 publications
17
207
10
7
Order By: Relevance
“…Cirrhosis has been reported to be a risk factor for ICC. 2,3,7,8,12,14) In essential agreement, we found worsening of liver fibrosis status (via chronic hepatitis to cirrhosis) to be associated with development of ICC. By univariate analysis, an elevated serum concentration of total bilirubin, elevated activities of aspartate aminotransferase and alanine aminotransferase, a decreased serum concentration of albumin, and a decreased platelet count were significant risk factors for ICC.…”
Section: Risk Factors For Icc Developmentsupporting
confidence: 82%
See 1 more Smart Citation
“…Cirrhosis has been reported to be a risk factor for ICC. 2,3,7,8,12,14) In essential agreement, we found worsening of liver fibrosis status (via chronic hepatitis to cirrhosis) to be associated with development of ICC. By univariate analysis, an elevated serum concentration of total bilirubin, elevated activities of aspartate aminotransferase and alanine aminotransferase, a decreased serum concentration of albumin, and a decreased platelet count were significant risk factors for ICC.…”
Section: Risk Factors For Icc Developmentsupporting
confidence: 82%
“…10,11) Indeed, the prevalence of HCV infection among ICC patients differs considerably among areas. 8,12) Where HCV infection is prevalent, it is an important pathogenetic factor in ICC. Although a high prevalence of HBV infection in ICC patients has been reported by the Liver Cancer Study Group of Japan (4.0% to 14.5%), 13) we did not find HBV infection to be an ICC risk factor in this study.…”
Section: Risk Factors For Icc Developmentmentioning
confidence: 99%
“…Cohort studies performed in the USA and Northern Europe all showed an increased risk of developing cirrhosis or HCC due to alcohol drinking, although some of them found a doseeffect relationship (Klatsky and Armstrong, 1992;Becker et al, 2002) whereas others found a threshold effect of 50-75 g/day, after which the risk does not increase further (Sorensen et al, 1998;Kamper-Jorgensen et al, 2004). Various factors may have caused these contrasting results, mainly confounding by other factors, inaccuracy in estimating the level of intake during follow-up, and the low power of the studies.…”
Section: Dose-effect Relationship and Threshold Of Safe Intakementioning
confidence: 99%
“…In fact, population-based cohort studies in North Europe showed that the risk of HCC was about 10-fold higher among subjects with hospital discharge diagnosis of cirrhosis, with or without alcoholism, compared to those with diagnosis of alcoholism without cirrhosis, suggesting that cirrhosis is a necessary intermediate for the development of HCC among subjects with alcoholism (Adami et al, 1992;Sorensen et al, 1998;Kuper et al, 2001). A role of alcohol in the absence of cirrhosis as a 'pure' carcinogen seems of minor importance.…”
Section: Dose-effect Relationship and Threshold Of Safe Intakementioning
confidence: 99%
“…Although ICC only represents 10% to 25% of primary liver cancers in most parts of the world, it is the most frequent subtype of liver cancer diagnosed in Thailand due to the extremely high prevalence of chronic liver fluke infestation, the major risk factor for ICC (2). Cirrhosis is also an important risk factor for ICC (6).…”
Section: Introductionmentioning
confidence: 99%